2020
DOI: 10.1038/s41598-020-78642-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of outdoor nature-related activities on gut microbiota, fecal serotonin, and perceived stress in preschool children: the Play&Grow randomized controlled trial

Abstract: Due to rapid urbanization, children today have fewer opportunities to interact with nature and this may result in a greater risk for developing stress and depression. Outdoor nature-related activities can enhance general well-being. However, the underlying mechanisms are not fully delineated. Here we recruited 54 preschool children to participate in a 10-week structured nature-related “Play&Grow” program. Following the intervention, children were assessed for connectedness to nature and perceived stress le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 55 publications
2
79
0
1
Order By: Relevance
“…The positive changes in the Prosocial scores of participants in the IG after the Play&Grow intervention are in agreement with the recently published study measuring gut microbiome [15], where the Play&Grow program significantly improved the overall perceived stress, particularly anger frequency and prosocial behavior of children, and suggested a mechanistic link between these behaviors and the bacterial load when children are exposed to natural environments. Likewise, beneficial impacts of exposure to the natural environment on negative emotions (i.e., anger and sadness) was also highlighted in a systematic review [23].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The positive changes in the Prosocial scores of participants in the IG after the Play&Grow intervention are in agreement with the recently published study measuring gut microbiome [15], where the Play&Grow program significantly improved the overall perceived stress, particularly anger frequency and prosocial behavior of children, and suggested a mechanistic link between these behaviors and the bacterial load when children are exposed to natural environments. Likewise, beneficial impacts of exposure to the natural environment on negative emotions (i.e., anger and sadness) was also highlighted in a systematic review [23].…”
Section: Discussionsupporting
confidence: 90%
“…The rationale and earlier results are described in greater detail in the protocol and other publications [3,15,17,18]. Play&Grow is a structured intervention aimed at improving urban preschoolers' connectedness to natural environments through interactive games for children and providing guidance for parents/caregivers on taking care of their children.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Bassingthwaighte (2017): Taking dramatherapy into the outside space: The benefits and obstacles when working with children with SEMH issues Berger (2006): Using contact with nature, creativity and rituals as a therapeutic medium with children with learning difficulties: A case study Kern and Aldridge (2006) (Gray and Birrell, 2015;Gray and Thomson, 2016;Tiplady and Menter, 2021). The duration also varied from 45 min (Sobko et al, 2020) to one full day (Tiplady and Menter, 2021;. The frequency and intensity varied from two consecutive days (Adams and Beauchamp, 2018Arbuthnott and Sutter, 2019) to once a week (Murphy, 2018;Sobko et al, 2020;Tiplady and Menter, 2021;.…”
Section: Authors and Study Titlementioning
confidence: 99%
“…The native microbial composition is not only strongly associated with host factors [2] but also with geographic and environmental variables [4,5]. Physical interactions between hosts and their natural environment may also alter the microbiota diversity and composition [6]. Recent work on the microbiota of humans and animals has suggested that, due to interactions, such as contact with natural environments and co-housing conditions, individuals may share specific bacterial strains or have a more similar microbiota with each other and their environments [7].…”
Section: Introductionmentioning
confidence: 99%